Applications of N,N'-Disubstituted-1,8-Diaminonaphthalene as a Scaffold to Support Group 13 Compounds, Carbenes and Pd(II) Carbene Complexes - Lee, Sojung (Université d'Ottawa / University of Ottawa, 2017)
This work is mainly concentrated on the development of new versatile ligand based on N,N’-disubstituted-1,8-diaminonaphthalene (1,8-DAN) for main group chemistry. Therefore, our initial efforts were made on the design of new ligand scaffold by using 1,8-DAN. Following that, new ligand family supported by 1,8-DAN was applied as ligands to main group elements (B, Al, In, Ga, and C). Furthermore, six-membered ring carbenes which are derived from the reaction between N,N’-disubstituted-1,8-diaminonaphthalene and carbon are also investigated. In addition, the stable carbenes were implied as a new ligand system for palladium, leading to the formation of metal ligand complexes. Therefore, the synthesis and reactivity of these complexes are also reported. Chapter I gives an explanation on the basic concepts in terms of the ligand designs and reports the reasons why N,N’-disubstituted-1,8-diaminonaphthalene has been chosen as the framework of for these ligands. Chapter II presents the approach to synthesize ligands depending on the substitution. Regarding this, three methods were successfully used: reductive amination, application of acyl halide followed by reduction, and copper catalyzed C-N coupling reactions. Chapter III describes the reactions between the N,N’-disubstituted-1,8-diaminonaphthalene and main group elements B, Al, Ga, and In in 13 group. In this chapter, a variety of mononuclear and dinuclear complexes are investigated and fully characterized. Furthermore, some computational studies are also reported for the comparison with experimental results. Chapter IV deals with new ligand family, carbene, which is derived from N,N’-disubstituted-1,8-diaminonaphthalene. Therefore, not only fundamental concepts for the NHC (N-heterocyclic carbene) are discussed but also synthetic pathways are introduced. Moreover, interesting features of free carbene are presented as well. Chapter V reports the potential of this new carbene ligand family as ligands for transition metal compound, especially, Pd(II) compounds. Several different pathways for synthesizing the desired metal carbene complexes are presented.
Keywords: Carbene; Perimidine Based Carbene; 1,8-DAN; N,N'-Disubstituted-1,8-Diaminonaphthalene; Main Group; Transition Metal